Ecclesiological implications for the church as intergenerational space focusing on families - P.R. Mans; P.A. Rosseau (Acta Theologica)
The church is God’s primary vehicle to minister in a global landscape dotted with globalisation, social media, wars, environmental issues, global economics, global social developments, and politics. Given the fact that the family is the microcosm where discipling should take place according to Psalm 78:4-7 (also Deut. 6:7-9; Matt. 28:19-20; 1 Cor. 3:4-9), this focus naturally leads to the critical question: Where do families fit in this mandate? Segregation in ministry results in divided age groups, lack of inclusiveness of all members in all of church life, and a low view of children as part of the church (Holmes et al. 2022:1-3). The article revisits a biblical framework of what church should be, in order to refresh insight into how the church could and should respond to an intergenerational understanding of the form and function of the church.